A review of the Angolan House snakes, genus Boaedon Duméril, Bibron and Duméril (1854) (Serpentes: Lamprophiidae), with description of three new species in the Boaedon fuliginosus (Boie, 1827) species complex. Issue 1 (31st August 2020) - Hallermann, Jakob; Ceríaco, Luis MP; Schmitz, Andreas; Ernst, Raffael; Conradie, Werner; Verburgt, Luke; Marques, Mariana P; Bauer, Aaron M
ABSTRACT: An integrative taxonomic review of the genus Boaedon in Angola is provided. A molecular phylogeny, based on 99 genetic samples for which the mitochondrial markers 16S rRNA have been sequenced, reveals 23 monophyletic species-level groups in Africa and indicates the presence of nine species in Angola. Based on both phylogenetic and morphological data, we revalidate and designate a neotype for B. angolensis, describe three new species for Angola (e.g. B. bocagei sp. nov., B. branchi sp. nov., and B. fradei sp. nov.), revalidate B. variegatus from its synonymy with B. lineatus and designate a lectotype for this taxon, and identify B. lineatus var. lineolatus as a junior synonym of B. variegatus . The taxonomic status of the recently described B. paralineatus from Central Africa is discussed with respect to the more inclusive B. lineatus group. Moreover, we report on a new country record for Angola, namely B. mentalis, which we elevate here to full species and discuss the taxonomic status of this species in southern Africa. Finally, we provide an identification key and updated distribution maps for all Boaedon species occurring in Angola, including the Cabinda enclave.